2002
DOI: 10.1023/a:1015295025950
|View full text |Cite
|
Sign up to set email alerts
|

Coping self‐efficacy perceptions as a mediator between acute stress response and long‐term distress following natural disasters

Abstract: The mediating effect of coping self-efficacy (CSE) perceptions between acute stress responses (ASR) and 1-year distress following two disasters was tested. Between 3 and 8 weeks after the second disaster and again at 1 year, 46 residents completed questionnaires. Posttraumatic Stress Disorder (PTSD) symptoms and global distress served as outcomes. Multiple regression demonstrated that ASR and Time I CSE were significant predictors of both Time 1 outcomes. Time 1 PTSD symptoms and Time 2 CSE were significant fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
190
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(221 citation statements)
references
References 38 publications
(14 reference statements)
23
190
2
6
Order By: Relevance
“…A recent prospective study conducted on firefighter training graduates found that high levels of hostility and low levels of selfefficacy at baseline (before exposure to traumatic on-thejob events) related to PTSD symptoms 2 years later [70]. Results are consistent with those from earlier studies establishing associations between high hostility and anger, reduced self-efficacy, and PTSD and further suggest that these characteristics are factors that predict PTSD [71][72][73][74][75][76][77]. A recent study has also suggested that PTSD in firefighters relates to pretrauma degree of catastrophic thinking [78].…”
Section: Predictive Factorssupporting
confidence: 80%
“…A recent prospective study conducted on firefighter training graduates found that high levels of hostility and low levels of selfefficacy at baseline (before exposure to traumatic on-thejob events) related to PTSD symptoms 2 years later [70]. Results are consistent with those from earlier studies establishing associations between high hostility and anger, reduced self-efficacy, and PTSD and further suggest that these characteristics are factors that predict PTSD [71][72][73][74][75][76][77]. A recent study has also suggested that PTSD in firefighters relates to pretrauma degree of catastrophic thinking [78].…”
Section: Predictive Factorssupporting
confidence: 80%
“…Involving at-risk populations in planning can also decrease the negative psychological impact of disasters by fostering a sense of coping self-efficacy-one's sense of being able to manage the demands of posttraumatic recovery (Benight & Harper, 2002). When plans are made without respect for these concerns, however, the community may spend additional resources that further delay its ability to rebound quickly and effectively.…”
Section: Potential Steps: Local Planners Should Establish Working Commentioning
confidence: 99%
“…In addition, over the past 20 years, a large body of research has accumulated that shows that psychosocial resources, such as hardiness, perceived control, and social support afford critical protection to disaster victims [40]. Furthermore, the results of research by Benight and Harper [45] showed that coping in terms of self-efficacy, lost resources, social support, optimism and demographic variables strongly predict distress during the on-set of disaster.…”
Section: Factors Influencing Vulnerabilitymentioning
confidence: 99%